Effects of Natural Convection and Radiation on MHD Stagnation Point Nano-Fluid Flow past a Stretchable Surface with Velocity Slip and Newtonian Heating - Gifty, G.P.; Padhi, S.B.; Mahatha, B.K.; Mahato, G.K. (East European Journal of Physics, 2025)
MHD stagnation point natural convection flow of a viscous, incompressible, electrically conducting, and heat radiating nanofluid past a stretchy surface with velocity slip and Newtonian heating in the presence of a transverse magnetic field is examined. Governing nonlinear partial differential equations are solved with the help of Matlab’s bvp4c technique. To confirm robustness and accuracy of the result, the numerical findings in this study are compared with the existing literature, and they are found to be in good agreement. Effects of various parameters on velocity, temperature, and species concentration are computed and presented in the form of graphs whereas the effects on skin friction, the heat transfer rate and mass transfer rate are tabulated. As a result of enhanced thermal energy accumulation or diffusion, nanofluid temperature is increased by Brownian motion, thermophoretic diffusion, velocity slip, convective heating, nonlinear thermal radiation, and Prandtl number. Rate of heat transfer is getting enhanced by temperature ratio, convective heating, and thermal Grashof number due to increased thermal gradients and buoyancy-driven heat transport. Such nanofluid flows have the potential to be used in a number of heat transfer processes such as renewable energy devices including MHD power generators, etc.